On the origin and significance of composite particles in mudstones: Examples from the Cenomanian Dunvegan Formation. Issue 2 (27th October 2020) - Li, Zhiyang; Schieber, Juergen; Pedersen, Per Kent
Abstract: Despite the fact that mud‐dominated composite particles have increasingly been recognized as important components of marine mudstones, the characteristics, types and origins of these composite particles remain poorly understood. This incomplete understanding of critical mudstone parameters (for example, depositional grain size, composition at the particle scale and provenance) severely limits the ability to accurately interpret the conditions (for example, depositional environment and climate) under which these rocks were deposited. Herein, detailed petrographic analysis was conducted in core samples from a transect of contemporaneous proximal to distal deposits from the Cenomanian Dunvegan Formation, a fluvial‐dominated delta system in the Western Canada Sedimentary Basin. Within the well‐developed depositional framework, mud‐dominated composite particles can be tracked along the depositional profile of the Dunvegan Formation from the fluvial to the marine realm (from incised valley to distal prodelta). By following these particles from source (hinterland erosion) to sink (offshore deposition), the origin and dispersal of various types of mud‐dominated composite particles in marine mudstones can be unequivocally determined. Mud‐dominated composite particles derived from a wide range of origins are differentiated. Allochthonous mud‐dominated composite particles, supplied by rivers draining the hinterland, comprise volcanic rock fragments (vitric or felsic in composition), chert fragments, shale lithics (clay‐mineral‐rich or quartz‐rich in composition), metamorphic rock fragments and chlorite/siderite clasts. Autochthonous mud‐dominated composite particles include rip‐up clasts (argillaceous, sideritic or siliceous in composition) formed from intra‐basinal erosion and contemporaneous floccules. The recognition of mud‐dominated composite particles shows that the Dunvegan prodelta 'mudstones' are much coarser grained and more heterogeneous in terms of their petrographic composition than the grain size of their component minerals would suggest. Results of this study call for a critical reappraisal of the composition and actual grain size of mudstones in general. Recognition of mud‐dominated composite particles can provide valuable insights to unravel their provenance, transport history and depositional setting, and will greatly enhance their utility as palaeoenvironmental archives.